Celebrification and Branding New Female Religious Authority in Indonesia - Kirana Nur Lyansari (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2022)
Indonesian religious authority in the Post-Soeharto era has dramatically shifted from organization to individual. Previously, the two largest organizations Nahdlatul Ulama and Muhammadiyah, dominated religious authority. However, recently, the religious activities of the Indonesian Muslims have been influenced by celebrities who experienced a religious transformation (hijrah). These celebrities, who become more obedient and pious in daily life, are called ‘Hijrah actors’ as the same concept as ‘born-again Muslims.’ They have emerged as motivators, inspirators, and preachers who advise being more obedient to Indonesian Muslims. As a result, Indonesian Muslims have many choices to decide the religious authority to follow. This condition has caused the new actors of religious authority to use different strategies to gain the trust and support of Indonesian Muslims. This article is a case study that focuses on Peggy Melati Sukma. She was a former Indonesian celebrity who became a female preacher and da’wa actor (propagation of Islamic teaching). This article examines how Peggy built her religious authority. Data and information are gathered from social media, participating in Peggy’s da’wa activities, and analyzing her several autobiographies. This article finds that Peggy builds her female religious authority in Indonesia through five strategies: storytelling, promoting the Islamic lifestyle, sponsoring Islamic charity, use social media, and organizing religious community. Keywords: branding, celebrity, female preacher, religious authority